The general data protection regulation, the clinical trial regulation and some complex interplay in paediatric clinical trials - Dalrymple, H. W. (European journal of pediatrics, 2021)
Although a number of authors have commented upon the impact of the GDPR on clinical trial conduct, few have examined the specific setting of paediatric trials. Whilst the general principles are the same as those for adults, some additional considerations arise. The ages of consent relating to data privacy and clinical trial participation are different in a number of countries, but the distinction is often not recognised in non-drug trials. Accidental pregnancies in clinical trials always raise complexities, but these are amplified when the trial subject is a minor, and the processes described in clinical trial protocols rarely take account of GDPR requirements. This paper describes approaches which can be taken to ensure the rights of children are respected. Conclusion : The conduct of paediatric clinical trials within GDPR requirements is quite possible provided authors think carefully when drafting protocols. What is Known: • GDPR is applicable to clinical trials, including paediatric trials. • A number of challenges at the interface between the GDPR and CTR have been described. What is New: • The application of the GDPR to certain specific situations in paediatric trials does not appear to have been explored. • Three such situations are described and solutions offered.